Lessons in diagnostic virology: expected and unexpected sources of error. (30th May 2019) - van Zyl, Gert; Maritz, Jean; Newman, Howard; Preiser, Wolfgang
Summary: Viral diagnostics have shown continued innovation, with serological and molecular diagnostic assays pushing the limits of sensitivity. Technology has provided new automated shared diagnostic platforms that reduce hands‐on time, while with globalisation of the diagnostic market, commercial assays are applied across epidemiologically diverse settings on different patient and viral populations. However, with these novel developments, new and often unexpected sources of diagnostic error emerge. In this review we will reflect on case studies that highlight these often underappreciated or unexpected diagnostic errors spanning pre‐analytical, analytical, and post‐analytic processes. We will also suggest approaches that could help identify error and reduce the impact on patient management.